2021
DOI: 10.1021/acs.jafc.1c02649
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Aroma Release and Dynamic Sensory Perception of Composite Foods

Abstract: Condiments such as spreads, dressings, or sauces are usually consumed together with carrier foods such as breads or vegetables. Dynamic interactions between condiments and carriers occur during consumption, which can influence aroma release and perception. This study investigated in vivo aroma release (PTR-MS) and dynamic sensory perception (time–intensity) of mayonnaises spiked with lemon aroma (limonene, citral). Mayonnaises were assessed without and with carrier foods (bread, potato).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 50 publications
5
24
0
Order By: Relevance
“…In our study, it may be that due to its lower moisture content, the wafer might have required an increased mastication time. Overall, our findings are in agreement with previous studies that demonstrated that toppings assisted saliva in bolus formation of different solid foods (bread, crackers, pasta, milk gels), leading to shorter oral processing times (Gonzalez-Estanol, Libardi, et al, 2022;van Eck et al, 2019). It should be noted that the TDS curves were not time standardized.…”
Section: Characterization Of Participants According To Their Habitual...supporting
confidence: 92%
See 4 more Smart Citations
“…In our study, it may be that due to its lower moisture content, the wafer might have required an increased mastication time. Overall, our findings are in agreement with previous studies that demonstrated that toppings assisted saliva in bolus formation of different solid foods (bread, crackers, pasta, milk gels), leading to shorter oral processing times (Gonzalez-Estanol, Libardi, et al, 2022;van Eck et al, 2019). It should be noted that the TDS curves were not time standardized.…”
Section: Characterization Of Participants According To Their Habitual...supporting
confidence: 92%
“…In general, our findings regarding the temporal sequence of dominant sensations of composite foods are in agreement with previous studies where different solid carriers (bread, wafer, carrots) were combined with various toppings (hazelnut-chocolate spread, mayonnaise). At the beginning of consumption, sensations related to the flavor and texture of the carriers were dominant, whereas sensations related to the toppings were dominant at later stages of consumption (Gonzalez-Estanol, Cliceri, et al, 2022;van Eck et al, 2019).…”
Section: Impact Of Habitual Eating Speed On Dynamic Sensory Perceptionmentioning
confidence: 99%
See 3 more Smart Citations